Magnetic Fields in Diffuse Media - Lazarian, Alexander; de Gouveia Dal Pino, Elisabete M.; Melioli, Claudio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This volume presents the current knowledge of magnetic fields in diffuse astrophysical media. Starting with an overview of 21st century instrumentation to observe astrophysical magnetic fields, the chapters cover observational techniques, origin of magnetic fields, magnetic turbulence, basic processes in magnetized fluids, the role of magnetic fields for cosmic rays, in the interstellar medium and for star formation. Written by a group of leading experts the book represents an excellent overview of the field. Nonspecialists will find sufficient background to enter the field and be able to appreciate the state of the art.
Future Observations of Cosmic Magnetic Fields with LOFAR, SKA and its precursors -- Magnetic fields with the Atacama Large Millimeter/submillimeter Array -- Synchrotron radiation and Faraday rotation -- Interstellar Grain Alignment – Observational Status -- Magnetic Field Measurement with Ground State Alignment -- Kinetic Turbulence -- Interstellar Polarization and Magnetic Turbulence -- MHD Turbulence and its Implications -- The intermittency of ISM turbulence : what do the observations tell us? -- Ambipolar Diffusion -- Magnetic Reconnection in Astrophysical Environments -- Interstellar MHD Turbulence and Star Formation -- Observations of Magnetic Fields in Molecular Clouds—Testing Star Formation Theory -- Magnetic Fields in Star Formation -- Particle Acceleration by Magnetic Reconnection -- Cosmic Ray transport in turbulent magnetic field -- Magnetic Fields in the Milky Way -- Magnetic fields in galaxies -- Simulations of galactic dynamos -- Cosmic rays in galaxy clusters and their interaction with magnetic fields -- Turbulence in the intracluster medium.
Keywords: Astronomy; Astrophysics; Plasma (Ionized gases).; Astronomy, Astrophysics and Cosmology; Plasma Physics